A practice perspective on strategic communication: the discursive legitimization of managerial decisions. Issue 3 (1st August 2016) - Aggerholm, Helle Kryger; Asmuss, Birte
Abstract : Purpose: In this paper, we intent to link the authentic, communicative activities, e.g. organization-wide meetings at the micro-level, to the institutionalized practices at the macro-level within an organization, e.g. change management decisions and communication strategy (Steyn, 2003). Thus, our concern is with the relationship between institutionalized strategic management and the real-life strategic communication processes, thus advancing our understanding of the role of texts and discourses in the actual practice of strategic communication in an organizational context of strategic change processes. Design/methodology/approach: The data is based on a large corpus of video-taped management meetings and organization-wide meetings in a large Danish public, knowledge-based organization. The method applied for studying the management discourse is a conversation analytical approach (Sacks et al., 1974; Sidnell, 2010). This method has been chosen as it enables us to focus on micro aspects of organizational practices (Nicolini, 2013) by investigating the interactional patterns that serve as resources for doing legitimation as an institutionalized practice. Findings: The common denominator for the entire analysis is legitimation accomplished through the discursive use of distanciation and the analysis identifies three different discursive elements or micro-level strategies directly related to the concrete doing of strategic communication. Firstly, legitimation is created by reference to the socio-economic context of the organization. Secondly, legitimation is generated by means of pointing to the abnormality of the strategic situation. And thirdly legitimation is fostered by the use of idiomatic expressions. These different ways of accomplishing legitimacy are in a strategy-as-practice perspective related to the specific, in-situ communicative praxis and accomplished by the concrete actions of the strategic communicators, and thus we can position the instances of strategic communication at the organizational micro-level. Originality/value: This paper studies at a micro level how strategic actors use various discursive resources to legitimize strategic decisions and how these resources constitute the discursive basis of strategic communication as a managerial practice. We focus on the role of discourse in the legitimization processes of strategic managerial decisions analyzing micro level instances of organizational communication. The paper thereby links the actor process activities (Langley, 2007), e.g. organization-wide meetings at the micro level, to the institutional field practices at the macro level within an organization, e.g. strategy and planning (Johnson et al., 2007).